Mutaciones clorofílicas inducidas por radiación Gamma en Phaseolus vulgaris L. - Meoño, María Eugenia (Revista de Biología Tropical, 1975)
In a study of chlorophyll mutants of Phaseolus vulgaris L. through Co60 gamma radiation, five types of mutants, classified as albino, cream, yellow, yellow-green and light green were obtained; all were lethal; their segregation was always proportionally lower than the Mendelian. Gamma radiation-induced mutations in black beans do not depart significantly from those obtained elsewhere in barley and wheat.